2018
DOI: 10.1111/febs.14589
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum quality control by garbage disposal

Abstract: Various types of intracellular and extracellular stresses disturb homeostasis in the endoplasmic reticulum (ER) and, thus, trigger the ER stress response. Unavoidable and/or prolonged ER stress causes cell toxicity and occasionally cell death. The malfunction or death of irreplaceable cells leads to conformational diseases, including diabetes mellitus, ischemic diseases, metabolic diseases, and neurodegenerative diseases. In the past several decades, many studies have revealed the molecular mechanisms of the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 81 publications
(98 reference statements)
0
22
0
Order By: Relevance
“…Alternatively, autophagy and apoptosis work together and cell dies for both mechanisms (Figure 1C). The subcellular compartments where autophagy and apoptosis could be interconnected are the endoplasmic reticulum [16], mitochondria [17] and lysosomes [18].…”
Section: Cross-talk Between Autophagic Apoptotic and Necrotic Patmentioning
confidence: 99%
“…Alternatively, autophagy and apoptosis work together and cell dies for both mechanisms (Figure 1C). The subcellular compartments where autophagy and apoptosis could be interconnected are the endoplasmic reticulum [16], mitochondria [17] and lysosomes [18].…”
Section: Cross-talk Between Autophagic Apoptotic and Necrotic Patmentioning
confidence: 99%
“…Autophagy and proteasomal degradation were examined because they are the cellular mechanisms responsible for removing misfolded protein from the ER. ( 30 ) Previously, we showed that mutant‐COMP accumulation in the ER of murine MT‐COMP growth plate chondrocytes occurs because autophagy was blocked by elevated mTORC1 signaling. ( 4 ) It remains unclear whether proteasome degradation plays a role in this ER‐stress‐induced chondrocyte pathology because the COMP‐ECM matrix within the ER may prohibit translocation from the ER to the proteasome.…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy and proteasomal degradation were examined as they are the cellular mechanisms responsible for removing misfolded protein from the ER (30) . Previously, we showed that MT-COMP accumulation in the ER of murine MT-COMP growth plate chondrocytes occurs because autophagy was blocked by elevated mTORC1 signaling (4) .…”
Section: Resveratrol Treatment Reactivates Autophagy In Mt-comp Chondmentioning
confidence: 99%
“…Autophagy and proteasomal degradation were examined as they are the cellular mechanisms responsible for removing misfolded protein from the ER (33) . Previously, we showed that MT-COMP accumulation in the ER of murine MT-COMP growth plate chondrocytes occurs because autophagy was blocked by elevated mTORC1 signaling (4) .…”
Section: Resveratrol Treatment Reactivates Autophagy In Mt-comp Chondmentioning
confidence: 99%